2021
DOI: 10.1126/science.abe2218
|View full text |Cite
|
Sign up to set email alerts
|

3D genomics across the tree of life reveals condensin II as a determinant of architecture type

Abstract: We investigated genome folding across the eukaryotic tree of life. We find two types of three-dimensional (3D) genome architectures at the chromosome scale. Each type appears and disappears repeatedly during eukaryotic evolution. The type of genome architecture that an organism exhibits correlates with the absence of condensin II subunits. Moreover, condensin II depletion converts the architecture of the human genome to a state resembling that seen in organisms such as fungi or mosquitoes. In this state, centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
185
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(216 citation statements)
references
References 111 publications
16
185
0
Order By: Relevance
“…The P. bachei genome assembly was recently scaffolded using Hi-C data ( Hoencamp et al 2021 ). The new, scaffolded assembly did not include a genome annotation.…”
Section: Methodsmentioning
confidence: 99%
“…The P. bachei genome assembly was recently scaffolded using Hi-C data ( Hoencamp et al 2021 ). The new, scaffolded assembly did not include a genome annotation.…”
Section: Methodsmentioning
confidence: 99%
“…This short comparison, supported by our models, indicates that the spatial chromosome length might be a valuable parameter to describe chromosome organization. Recently, lengthwise compaction of mitotic chromosome was also proposed to determine the subsequent architecture in interphase ( 27 ). More data are required to confirm our observations, but we expect that future studies could relate chromosome organization to its length observed by chromosome imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In mitotic chromosomes, cohesins are related to sister chromatid cohesion, while the condensation of chromosomes relies on the function of condensin I and II ( 26 , 27 ). In vertebrates, the two condensins have been associated with different phases of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Hoencamp and colleagues [67] have determined that homologs tend to be separated or paired across species depending on whether they carry functional condensin II subunits. Species lacking all or partial condensin II subunits (e.g., fruit flies and mosquitoes), exhibit Rabl-like architectural features (centromere clustering, telomere clustering, and a telomere-to-centromere axis), and tend to be homolog pairing.…”
Section: Features Of the Spatial Organization Of Homologous Chromosomesmentioning
confidence: 99%